Penyuluhan Kesehatan Kiat Menjaga Kesehatan Mental Pre Menopause dan Peningkatan Kapasitas Anggota Dharma Wanita Persatuan – DWP Kemenag Bantul - Prihastuti Prihastuti (Lembaga Pengembangan Kinerja Dosen, 2025)
Menopause is a natural process that occurs in all women, marked by the permanent cessation of menstruation (menstruation) and begins with irregular menstrual periods (Northrup, 2021). Often women face menopause with anxiety and fear because they are entering old age and are no longer able to give birth. Children (Sebtalesy & Irmawati Mathar, 2019). As a result of this situation, a decrease in the hormone estrogen, progesterone and sex hormones can cause physical symptoms that may be experienced when reaching menopause, namely in the form of a sudden hot feeling attacking the upper part of the body, excessive sweating at night, difficulty sleeping, irritation of the skin, symptoms in the mouth and teeth, vaginal dryness, difficulty holding urine, and weight gain (Intan, 2017; Noervadila et al., 2020). The target of this Community Service (PKM) activity are mothers who are members of the Dharma Wanita Association – DWP, Bantul Ministry of Religion. This community service activity was carried out as an effort to improve the level of public health simultaneously and synergistically in Tips for Maintaining Pre-Menopausal Mental Health and Increasing the Capacity of Members of the Dharma WanitaSatu – DWP Ministry of Religion Bantul.